Nothing beyond the Material: Observations of a Pioneer of German Material Culture Studies (KULT_online, 2013)
The book Signaturen der Kultur (Signatures of Culture) is a collection of papers and articles by the anthropologist Martin Scharfe from the period between 1990 and 2007, which bore great impact on the methods of cultural analysis in German anthropology and paved the way for material culture studies. The author's ideas are based on the presumption that culture does not exist beyond the material. The focus lies on the questions of how history is imprinted in things and how the relation between man and objects can be described. Alongside examples from eighteenth- and nineteenth-century literature, art, and normative sources like treatises, the author develops the idea that things can be read as cultural markers, from which historical norms, praxes, thinking, and sentiment can be understood. Although all objects leave their maker and suffer changes in meaning or lose their formal integrity, the temporal signature of cultural precondition is still visible. The author defines the aim of historical research as the tracing and decoding of this signature.